2014 IEEE International Instrumentation and Measurement Technology Conference (I2MTC) Proceedings 2014
DOI: 10.1109/i2mtc.2014.6860870
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone based, portable optical biosensor utilizing surface plasmon resonance

Abstract: A portable low cost biosensor suited for future medical diagnostic application is presented. The device comprises a custom designed scaffold, a disposable polymeric chip for surface plasmon resonance (SPR) sensing, and a smartphone. This commercial telecommunication device provides both, the optical illumination required for triggering of the SPR phenomenon and established by its active-matrix of organic light-emitting diodes (i.e., the smartphone display), whereas optical detection is obtained by means of its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…Over couples of decades, SPR sensors had vast advances in terms of both technology development and their applications (Hoa et al, 2007;Homola, 2008;Zeng et al, 2014). For studies about biosensing with smartphone, SPR measurements were also carried out by coupling optical refractometric fabrication to smartphone on the basis of optical sensor design (Preechaburana et al, 2012;Souza Filho et al, 2014). Preechaburana et al reported a coupling of an angle-resolved SPR instrument to smartphone for dete ting of β 2 mi roglobulin (β 2 M), which was one of the very important biomarkers for cancers, inflammatory disorders, and kidney diseases.…”
Section: Smartphone-based Spr Biosensorsmentioning
confidence: 99%
“…Over couples of decades, SPR sensors had vast advances in terms of both technology development and their applications (Hoa et al, 2007;Homola, 2008;Zeng et al, 2014). For studies about biosensing with smartphone, SPR measurements were also carried out by coupling optical refractometric fabrication to smartphone on the basis of optical sensor design (Preechaburana et al, 2012;Souza Filho et al, 2014). Preechaburana et al reported a coupling of an angle-resolved SPR instrument to smartphone for dete ting of β 2 mi roglobulin (β 2 M), which was one of the very important biomarkers for cancers, inflammatory disorders, and kidney diseases.…”
Section: Smartphone-based Spr Biosensorsmentioning
confidence: 99%
“…In several biosensing cases, smartphones were also used to replace scientific instruments to detect biomolecular bindings (Boero et al, 2014;Liu et al, 2014;Roda et al, 2014). Various sensor techniques such as fluorescence, electrochemistry and plasmonic resonance was linked to smartphones progressively and used in biodetections for targets such as bacteria and biomarkers (Jiang et al, 2014;Rajendran et al, 2014;Roda et al, 2014;Souza Filho et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Dentre as diversas aplicações existentes com smartphones pode-se citar: biossensores baseados em Ressonância de Plasmon de Superfície (RPS) (Souza Filho et al, 2014;Preechaburana et al, 2012) , detecção do pesticida glifosato utilizando biossensor RPS (d. Silva Freire et al, 2019),análise de interações cinéticas entre proteínas , um sensor de temperatura (Lu et al, 2019), a detecção de anticorpos da hepatite C utilizando potenciostato eletroquímico (Aronoff-Spencer et al, 2016), análise de qualidade daágua (Srivastava et al, 2018), detecção deácido lático no suor ou saliva (Roda et al, 2014), facilitação de imunoensaios através do biossensor GMR (Choi et al, 2016).…”
Section: Introductionunclassified
“…Neste trabalho o brilho da telá Neste artigo caracteriza-se o comportamento da fonte de luz gerada pela tela do smartphone.3. DESCRIÇÃO DA PLATAFORMAO biossensor utilizado neste trabalhoé uma adaptação do projeto desenvolvido por(Souza Filho et al, 2014). A plataforma desenvolvida está ilustrada na Figura 2.…”
unclassified